Formulation of Composite Flour Made from Wheat, Maize Sprout, and Seaweed for Dried Noodle Production - Jannah, Roudotul; Sukatiningsih, Sukatiningsih; Diniyah, Nurud (Jurnal Teknologi Pertanian, 2014)
The aim innovation of noodle production by maize sprout and seaweed are to decrease utilization of wheat with exploited local commodity. In order to defend elasticity in noodle characteristic, seaweed’s flour as gelling agent can be added. This research consist of some stages i.e flour’s production, formulation, noodle’s production, selection of two formulas by hedonic scale test and observation of phisyco-chemical characteristic as noodle selected by hedonic scale test. The proportion of wheat flour and maize sprout flour was consist of 90% wheat and maize sprout flour. The ratio of wheat and maize sprout flours are 8:1 (P1), 7:2 (P2), 6:3 (P3), 5:4 (P4), 4:5 (P5). Seaweed flour which is  added in dried noodle’s batter is 10% at all treatment. As the control, batter made from 100% wheat flour. Based on hedonic scale test, value of color, taste, elasticity, and overall sensory characteristic are significantly different in all treatment of dried noodle’s formula. Value of aroma are not significantly different (ns) by hedonic scale test. The dried noodles made by formula of 80% wheat, 10% maize sprout, 10% seaweed and formula 70% wheat, 20% maize sprout, 10% seaweed were selected as best treatment by hedonic scale test. The flour’s proportion were significantly influence to content of ash, protein, carbohydrate, water holding capacity, cooking loss, ligthness and antioxidant activity. The difference flour’s proportion was not significantly influence  to the content of moisture and fat. Keywords: Antioxidant activity, cooking loss, dried noodle,  maize sprout, seaweed.